The impact on the Development of Ukrainian-Polish Humanitarian Cooperation - Strilchuk, Lyudmila; Стрільчук, Людмила (My University, 2015)
The article analyzes the Ukrainian-Polish intergovernmental cooperation in tourism and its impact on the activation of humanitarian cooperation of neighboring countries. It is thanks to bilateral cooperation in the tourism sector is expanding international relations, depening knowledge of the neighboring country, its culture, traditions, history, erased the negative social and historical stereotypes, forming a positive image of the country neighbor, and this is turn leads to inter-ethnic reconciliation, establishing good neighborly relations. Ukrainian-Polish border is especially rich common historical and cultural monuments. However, in the last decade Ukrainian-Polish Tourist cooperation goes far beyond the border regions, covering more and more territory, attracting more and more tourists from both countries.
Вплив туризму на розвиток українсько-польського гуманітарного співробітництва
Keywords: tourism; humanitarian cooperation; state border; inter-state relations; Ukraine; Poland